"The relationship between corporate directors' disclosure and insider trading cases" - Shaima Ghaleb Al-Azzawi (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
Disclosure and transparency is one of the Basic elements of corporate governance. corporate governance is a system developed in common law systems (English and American laws). It is no coincidence that this system has a legal and legislative basis. These systems started as judicial applications and later evolved into a separate chapter for companies laws. and titled under the name of corporate governance, the legal dimension of the term is much deeper than the perception of some, and the reason for the emergence of a similar perception, that the systems of civil law, which are mostly affected by the Latin school (in French law) separate the law from the business, while the common law systems are devoted to the idea of business laws, including, of course, corporate governance in all of its aspects, In this paper We will try to shed light on the duty of disclosure ,Which is the responsibility of the company's managers, and their violation is to encourage monopolistic actions and Insider Dealing in the markets and stock exchanges, through a quick review of Fiduciary duties. The requirements is duty of loyalty and the duty of care), Then the American jurisprudence added new duties: (the duty of disclosure, extra care when your company is a takeover target, or Mergers, when managers and employees in the companies do any behavior that would harm the interests of shareholders or minority, is contrary to these principles of credit transactions such as Insider trading, or not disclose material information for the purposes of achieving profit Or personal gain.